IKKβ-Targeted Anti-Inflammatory Activities of a Butanol Fraction of Artificially Cultivated Cordyceps pruinosa Fruit Bodies. (15th July 2014) - Kim, Han Gyung; Yang, Woo Seok; Sung, Gi-Ho; Kim, Ji Hye; Baek, Gwang-Soo; Kim, Eunji; Yang, Sungjae; Park, Yung Chul; Sung, Jae Mo; Yoon, Deok Hyo; Kim, Tae Woong; Hong, Sungyoul; et al.
Abstract : The inhibitory activities of the Cordyceps pruinosa butanol fraction (Cp-BF) were investigated by determining inflammatory responses of lipopolysaccharide (LPS)-treated RAW264.7 macrophage cells and by evaluating HCl/ethanol (EtOH)-triggered gastric ulcers in mice. The molecular mechanisms of the inhibitory effects of Cp-BF were investigated by identifying target enzymes using biochemical and molecular biological approaches. Cp-BF strongly inhibited the production of NO and TNF- α, release of reactive oxygen species (ROS), phagocytic uptake of FITC-dextran, and mRNA expression levels of interleukin (IL)-6, inducible NO synthase (iNOS), and tumour necrosis factor-alpha (TNF)- α in activated RAW264.7 cells. Cp-BF also strongly downregulated the NF- κ B pathway by suppressing IKK β according to luciferase reporter assays and immunoblot analysis. Furthermore, Cp-BF blocked both increased levels of NF- κ B-mediated luciferase activities and phosphorylation of p65/p50 observed by IKK β overexpression. Finally, orally administered Cp-BF was found to attenuate gastric ulcer and block the phosphorylation of I κ B α induced by HCl/EtOH. Therefore, these results suggest that the anti-inflammatory activity of Cp-BF may be mediated by suppression of IKK α and its downstream NF- κ B activation. Since our group has established the mass cultivation conditions by developing culture conditions for Cordyceps pruinosa, the information presented in this study may be useful for developing new anti-inflammatory agents.